The assessment of angiogenic factors VEGF, VEGFR-2 and VCAM-1 in the serum of women with malignant ovarian tumours before and after the menopause - Czekierdowski, Artur; Czekierdowska, Sylwia (Menopause Review/Przegląd Menopauzalny, 2007)
Aim: The aim of this study was to evaluate preoperative serum concentrations of selected soluble angiogenic cytokines in women with malignant ovarian tumours. Material and methods: we investigated clinical and pathological characteristics of 77 women (43 after the menopause) with ovarian cancer and compared the results with VEGF, VEGFR-2 (receptor to VEGF, type 2) and VCAM-1 serum concentrations using the ELISA method and R&D Systems (USA) kits. The differences were compared with chi square test. Results: Serum concentrations of VEGF and VEGFR-2 were higher in women after menopause (Z=–1.9; p=0.054 for VEGF and Z=–1.71; p=0.08 for VEGFR-2). Neither tumour histological grade nor FIGO clinical stage were related to the measured concentrations of these soluble cytokines. VCAM-1 concentration was not different between the groups of pre- and postmenopausal women. The highest concentrations of VCAM-1 were found in a subgroup of low histological grade and FIGO stage 3-4 tumours and the differences between these women and patients with high grade tumours and/or FIGO stage 1-2 cancers were statistically significant (H=10.7; p=0.004 and H=17.4; p=0.0006, respectively). Conclusion: Measurements of the soluble forms of VEGF and VEGFR-2 in blood serum are probably not useful in preoperative malignant ovarian tumour management. VCAM-1 concentrations may be of value as an additional marker of ovarian cancer angiogenic characteristics, possibly related to histological grade and clinical stage.